CURRENT ISSUES OF IMPLEMENTING THE ASTREINTE INSTITUTION: ENHANCING THE EFFICIENCY OF COURT DECISION ENFORCEMENT IN UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Ensuring the proper fulfillment of obligations by subjects of civil law is one of the most important and controversial issues both in the theory of domestic and foreign civil law and in the practice of law enforcement. In this regard, the scientific study of specific methods of ensuring the fulfillment of obligations is of great importance, many of which are gradually finding their expression in the legislation of the Republic of Uzbekistan. However, due to the lack of practical experience and the scarcity of theoretical sources, their essence, relevance and necessity of application are causing serious debate in the scientific and legal community. The Astreinte Institute stands out as one of such institutions. This article is devoted to considering some problematic aspects of determining the theoretical essence of the astreinte institute, as well as issues that may affect the subsequent amendments to the text of relevant regulatory legal acts of the Republic of Uzbekistan. The main purpose of the analytical article is to try to comprehensively determine the theoretical essence of the astreinte institution and its most important legal features.